COMPARISON OF IMPLANT DENSITY IN THE MANAGEMENT OF LENKE 1B AND 1C ADOLESCENT IDIOPATHIC SCOLIOSIS - Kilinc,Bekir Eray (2019)
ABSTRACT Objective: To compare radiographic and surgical outcomes of Lenke 1B and 1C patterns. Methods: One hundred twenty patients with Lenke 1B and 1C scoliosis were grouped according to implant density as follows: low density (LD) of ≤1.4 and high density (HD) of >1.4. Matched subgroups (30 patients each) based on age, curve magnitude, and body mass index (BMI) were analyzed. Radiographic parameters were evaluated before operation, immediately after operation (ipo), and at 2 years’ follow-up. SRS-30 was administered before operation and at 2 years’ follow-up. Results: The major curves of the LD (n = 82) and HD groups (n=38) were respectively 59.1° and 65.6° before operation (p <.001), 26.3° and 22.9° ipo (p =.05), and 29.9° and 19.8° at 2 years’ follow-up (p <.001). No significant differences in postoperative trunk shift and coronal balance were found (p =.69 and p =.74, respectively). The HD group had higher blood loss (p =.02), number of implants (p <.001), levels fused (p =.002), and surgical time (p <.001). The HD group had a higher prevalence of hypokyphosis from before operation to follow-up (p <.001). No significant differences were observed in the SRS-30 scores before operation and at 2 years’ follow-up. The matched groups had similar preoperative major curves (p =.56), ages (p =.75), and BMIs (p =.61). Significantly longer surgical time (p =.009), higher density (p <.001), and better correction (p =.0001) were found in the HD group at 2 years’ follow-up. No significant differences were found in the SRS-30 scores before operation and at 2 years’ follow-up. Conclusion: LD constructs included fewer segments fused, lower intraoperative estimated surgical blood loss, and shorter operation time, and potentially decreasing complication risks due to fewer implants. Level of evidence III, Retrospective Cohort Study.